(untitled) (Medico Legal Update, 2021)
The preference of ideal number of children among adolescents can predict future fertility rates and population growth. This study aims to analyze the determinants of preference of ideal number of children in adolescents aged 15-24 years in Indonesia. The method used in this study is descriptive with data analysis of IDHS 2017. The results show that the preference of ideal number of children among adolescents in Indonesia is 2.7 children. This figure increase from the average preference of ideal number of children in 2012 and is higher than the 2015 Total Fertility Rate, which is 2.28. Factors that influence the preference of ideal number of children among adolescent are the characteristics and socio-demographic background, exposure to media, and the discussion on adolescent reproductive health.